2015
DOI: 10.1007/s10509-015-2435-z
|View full text |Cite
|
Sign up to set email alerts
|

How does the oblateness coefficient influence the nature of orbits in the restricted three-body problem?

Abstract: We numerically investigate the case of the planar circular restricted three-body problem where the more massive primary is an oblate spheroid. A thorough numerical analysis takes place in the configuration (x, y) and the (x, E) space in which we classify initial conditions of orbits into three categories: (i) bounded, (ii) escaping and (iii) collisional. Our results reveal that the oblateness coefficient has a huge impact on the character of orbits. Interpreting the collisional motion as leaking in the phase s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 55 publications
5
16
0
Order By: Relevance
“…Strikingly enough similar behavior, regarding the influence of the oblateness coefficient on the character of the orbits, has also been reported in [69] and [71]. Therefore we may conclude that the oblateness of the primaries affects, in a very similar way, the nature of the orbits in both 2dof and 3-dof versions of the circular restricted three-body problem.…”
Section: Influence Of the Oblateness Coefficientsupporting
confidence: 82%
See 2 more Smart Citations
“…Strikingly enough similar behavior, regarding the influence of the oblateness coefficient on the character of the orbits, has also been reported in [69] and [71]. Therefore we may conclude that the oblateness of the primaries affects, in a very similar way, the nature of the orbits in both 2dof and 3-dof versions of the circular restricted three-body problem.…”
Section: Influence Of the Oblateness Coefficientsupporting
confidence: 82%
“…Our study complements previous works, where bounded, escape and collision motion was studied in a series of papers for the 2-dof RTBP (e.g. [69][70][71]).…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…In addition, the two exotic bugs with many legs and antennas still exist, corresponding to libration points L 1,7 and for other libration points the butterfly wings shaped region occur. It is observed that the geometry of the basins of convergence in the present case highly resembles to that of the classical case (see [22]).…”
Section: Case V: When Five Libration Points Existsupporting
confidence: 53%
“…Throughand it will never come back [6]. Our previous numerical experience (e.g., [53,54,55]) strongly suggests that the total orbital energy of the test-particle in the inertial frame becomes positive much sooner than it takes for the massless particle to cross the disk with radius R d = 10. Thus we may claim that our escape criterion used in the previous series of papers, and also in the present one, is both correct and safe.…”
Section: Methodsmentioning
confidence: 91%